2013
DOI: 10.1155/2013/858921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factor for Cardiovascular Disease Using Heart Rate Variability in Postmenopausal Women: A Comparative Study between Urban and Rural Indian Women

Abstract: Cardiovascular diseases are important causes of morbidity and mortality in postmenopausal women. A major determinant of cardiovascular health is the status of autonomic nervous system and assessment of Heart Rate Variability (HRV). Heart Rate Variability is a noninvasive and sensitive technique to evaluate cardiovascular autonomic control. Reduced HRV is an independent risk factor for the development of heart disease. This study evaluated the risk factors for cardiovascular diseases using HRV, between urban an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…2017;61/2 reduction of the gonads and steroid production (24). Estrogens play a key role in maintaining adequate levels of HDL-C (8).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…2017;61/2 reduction of the gonads and steroid production (24). Estrogens play a key role in maintaining adequate levels of HDL-C (8).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%
“…A study conducted with diabetic women found a high prevalence of MS in both premenopausal (87.5%) and postmenopausal (87.7%) women (24). Insulin resistance is described as a key factor implicated in the pathophysiology of MS (40).…”
Section: Metabolic Syndrome In Menopausal Womenmentioning
confidence: 99%
“…In addition to the reproducibility and low cost, this technique allows us to identify changes even in the subclinical stage and has a high prognostic value. As a result, the indices derived from this method have been used as health and disease biomarkers, as well as indicators of the effects of therapeutic interventions in several diseases, among them cardiovascular [16,17] , metabolic [18][19][20] and autonomic [21,22] disorders. Given the above, we conducted a review of acute and chronic effects of resistance training on the heart rate and cardiac autonomic regulation in the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…5 It is known that, regardless of the presence of pathological conditions, there has been a decrease in vagal modulation, as well as an increase in sympathetic activity and the sympatho-vagal ratio with aging, and that high values of high frequency spectral power ) Represent a protection factor. 6 For this reason, the indices derived from HRV analysis have been used as biomarkers of health status, disease and the effects of therapeutic interventions in several pathologies, among them, cardiovascular 7 metabolic ones 8 and autonomic. 9 Among the therapeutic strategies for the treatment of DM2, physical exercise has received great attention, since it is believed that physical exercise modulates cardiac autonomic control, decreasing the sympathetic influence and provoking greater vagal modulation, thus affecting positively the prognosis of individuals to A variety of morbidities.…”
Section: Introductionmentioning
confidence: 99%